2009
DOI: 10.1094/phyto-99-6-0765
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity and Evolutionary Processes of Alternaria solani in Brazil Inferred Using Genealogical and Coalescent Approaches

Abstract: Alternaria spp. form a heterogeneous group of saprophytic and plant-pathogenic fungi widespread in temperate and tropical regions. However, the relationship between evolutionary processes and genetic diversity with epidemics is unknown for several plant-pathogenic Alternaria spp. The interaction of Alternaria solani populations with potato and tomato plants is an interesting case study for addressing questions related to molecular evolution of an asexual fungus. Gene genealogies based on the coalescent process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…Isolates obtained from contiguous tomato and potato fields such as in Margahayu, Lembang, could possibly originate from a tomato field infected with an adapted lineage to this host. Other studies in the USA, Brazil and Cuba found population subdivision according to the host of origin as detected by RAPD and/or AFLP markers (Weir et al 1998;Martinez et al 2004;Lourenço et al 2011) as well as by sequence analyses of ITS region of rDNA and the genes encoding glyceraldehyde-3-phosphate dehydrogenase (gpd), and Alt a1 (Lourenço et al 2009). …”
Section: Aflp Polymorphism and Phylogenetic Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Isolates obtained from contiguous tomato and potato fields such as in Margahayu, Lembang, could possibly originate from a tomato field infected with an adapted lineage to this host. Other studies in the USA, Brazil and Cuba found population subdivision according to the host of origin as detected by RAPD and/or AFLP markers (Weir et al 1998;Martinez et al 2004;Lourenço et al 2011) as well as by sequence analyses of ITS region of rDNA and the genes encoding glyceraldehyde-3-phosphate dehydrogenase (gpd), and Alt a1 (Lourenço et al 2009). …”
Section: Aflp Polymorphism and Phylogenetic Analysismentioning
confidence: 96%
“…Previous studies revealed considerable variability among isolates with respect to morphology, physiology, biochemistry, aggressiveness and genetics (Bonde 1929;Henning and Alexander 1959;Petrunak and Christ 1992;Weir et al 1998;Castro et al 2000;Martinez et al 2004;van der Waals et al 2004;Varma et al 2006;Lourenço et al 2009;Lourenço Jr et al 2011;Weber and Halterman 2012;Meng et al 2015;Kumar et al 2016;Odilbekov et al 2016). Great variability in A. solani is unexpected, since the sexual stage of this pathogen is not known (Meng et al 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the etiology of the disease has been traditionally attributed to the fungus Alternaria solani Sorauer (ROTEM, 1994), in 2000 a new species was described, Alternaria tomatophila Simmons, is commonly associated with the black spot lesions on tomato plants (SIMMONS, 2000;LOURENÇO et al, 2009). In Brazil, it was demonstrated that the fungus A. tomatophilia is the etiologic agent of the disease (RODRIGUES et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Might be responsible for esophageal cancer. Greco et al, 2012;Gambale et al, 1976;Pollock et al, 1982;Biggs et al, 1993;Biggs, 1995;Gamboa-Angulo et al, 2000;Gamboa-Angulo et al, 2002;Andersen et al, 2008;Andrew et al, 2009;Lourenco et al, 2009;Alexander et al, 2011;Díaz Dellavalle et al, 2011;Somma et al, 2011;Edin, 2012;Pavón-Moreno et al, 2012;Benavidez Rozo et al, 2013 Aspergillus brasiliensis, A. costaricaensis, A. flavus, A. lacticoffeatus, A. nidulans and A. niger. Chaetocin, penitrem A, and xanthocillin , tenuazonic acid, aflatoxin G2, aflatoxin B1 and B2, chaetoglobosin C, ochratoxin A and spinulosin.…”
Section: Introductionmentioning
confidence: 99%